The The Role Of Organizational Behavior In Enhancing Employee Performance In The Modern Era: A Literature Review From Human Resource Management Perspective - Andi Nurfiana Haz (Journal of Studies in Academic, Humanities, Research, and Innovation, 2026)
The rapid advancement of digital technology, organizational transformation, and increasingly flexible work arrangements have significantly reshaped the dynamics of human resource management in modern organizations. In this context, organizational behavior has emerged as a strategic factor influencing work effectiveness, productivity, and organizational performance. This study aims to systematically examine the relationship between organizational behavior and employee performance from a Human Resource Management (HRM) perspective. The study employed a Systematic Literature Review (SLR) approach following the PRISMA guidelines. Literature was collected from Scopus, ScienceDirect, Emerald Insight, SpringerLink, Wiley Online Library, Taylor & Francis, and Google Scholar. An initial search identified 85 articles published between 2020 and 2025. After duplicate removal, title and abstract screening, and full-text eligibility assessment, 9 articles were selected for final analysis. The findings indicate that organizational culture, transformational leadership, work motivation, employee engagement, organizational communication, and digital technology utilization are the most frequently reported determinants of employee performance. Among the reviewed studies, employee engagement and transformational leadership emerged as the most consistently significant predictors of performance improvement across various organizational contexts. The review further reveals that organizational trust, effective communication, and digital leadership play critical roles in supporting employee productivity within hybrid and technology-driven work environments. This study contributes to the theoretical development of organizational behavior and provides practical implications for designing adaptive, innovative, and sustainable HRM strategies in the digital era.